2014
DOI: 10.3390/polym6041129
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Analysis of Stress Distribution in a Carbon Fiber-Reinforced Polymer Rod Bonding Anchor

Abstract: This paper presents an elastic shear stress distribution theoretical model at the carbon fiber-reinforced polymer (CFRP)-adhesive interface of a single-rod and a multi-rod straight-pipe bonding anchor. A comparison between theoretical and finite element analysis results reveals that the accuracy of the theory can be used to guide the preliminary design of CFRP rod bonding anchors. The mechanical performance of the inner cone bonding anchor for multi-rods are evaluated within different coefficients of friction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…Glass fiber-reinforced polymer (GFRP)-concrete composite structures have been widely used in infrastructure [1,2,3,4,5]. The connection between GFRP and concrete is of great importance.…”
Section: Introductionmentioning
confidence: 99%
“…Glass fiber-reinforced polymer (GFRP)-concrete composite structures have been widely used in infrastructure [1,2,3,4,5]. The connection between GFRP and concrete is of great importance.…”
Section: Introductionmentioning
confidence: 99%
“…CONTA174 and TARGE170 were used to simulate the follow-up and extrusion action between the load transfer medium and the steel sleeve. The FC at the interface between steel and resin is usually taken as 0.1–0.3 (Cai et al, 2016; Feng et al, 2014). Because the load transfer medium has varying stiffness, it is necessary to determine the appropriate FC to accurately evaluate the design parameters of the anchorage system with different cable capacities.…”
Section: Methodsmentioning
confidence: 99%
“…Numerous efforts from researchers [e.g. [10][11][12][13][14][15][16][17][18][19] came up with three basic types of anchorage systems for CFRP tendons with respect to load transfer mechanism, namely, (1) adhesively bonded anchorage system (such as in Fig. 1a), (2) mechanical clamping anchorage system (such as in Fig.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…They found that the cohesive zone model with progressive damage was the most reasonable for describing and predicting the approximate distribution of shear stress in the epoxy bonded anchorages among the other models. Feng et al [15] characterized the mechanical properties of single-rod and a multi-rod straight-pipe bonded anchorage by using the finite element method.…”
Section: Accepted Manuscriptmentioning
confidence: 99%